D'Holbach's Coterie : An Enlightenment in Paris - Kors, Alan Charles (Book collections on Project MUSE., 2015)
"Students of the Enlightenment have long assumed that the major movement towards atheism in the Ancien Regime was centered in the circle of intellectuals who met at the home of Baron d'Holbach during the last half of the eighteenth century. This major critical study shows, contrary to the accepted views, that in fact, atheism was not the common bond of a majority of the members and that, far from being alienated figures, most of the members were privileged and publicly successful citizens devoted to peaceful and gradual reform. Alan Charles Kors determines the coterie's membership and discovers it to have been a diverse assemblage of philosophes, men of letters, and scientists. Analyzing the thought and behavior of those members who lived past 1789, the author argues that the hostility to the Revolution expressed by the coterie's survivors was fully consistent with their world view."--